High-strength extremely thick steel plate and method for manufacturing same

By controlling the carbon equivalent and steel structure in an extremely thick steel plate with a plate thickness of more than 100mm, ensuring the formation of bainite and the fineness of grains, the problem of poor brittle crack propagation stop characteristics of the steel plate is solved, and high strength and excellent toughness are achieved.

CN119630827APending Publication Date: 2025-03-14JFE STEEL CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380059615.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-11-14
Filing Date
2023-08-30
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The prior art is difficult to achieve high-strength, excellent toughness and brittle crack propagation stop characteristics on extremely thick steel plates with plate thicknesses greater than 100 mm. Especially in ships and marine structures, the brittle crack propagation stop characteristics of steel plates are difficult to meet safety requirements.

Method used

By controlling the carbon equivalent (Ceq) to be more than 0.480%, it is ensured that the steel structure at 1/2 of the plate thickness becomes bainite on the entire surface, thereby improving the strength. Meanwhile, the ratio of bainite surrounded by grain boundaries with a grain size of 20 μm or less and an orientation difference of 15° or more is controlled, and the size of the pores is suppressed, so as to ensure that the equivalent circle diameter of the maximum pore is less than 200 μm.

Benefits of technology

On extremely thick steel plates with plate thickness greater than 100mm, the yield strength reaches more than 390MPa, the Champagne fracture transition temperature is below -100℃, and the Kca (-10℃) value reaches more than 8400N/mm3/2, meeting the requirements of high strength, excellent toughness and brittle crack propagation stop characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a high-strength extremely thick steel plate and a manufacturing method thereof. This high-strength extremely thick steel plate has a specific component composition, has a texture in which the X-ray intensity ratio of the (211) plane of the rolled surface at a position 1 / 2 of the plate thickness is 1.60 or more, and has a steel structure at a position 1 / 2 of the plate thickness, the steel structure at the 1 / 2 position of the sheet thickness is a mixed structure comprising 80-100% by area fraction of a bainite phase and 0-20% by area fraction of a ferrite phase, the average grain diameter of bainite grains surrounded by grain boundaries having an orientation difference of 15 degrees or more is 20 [mu] m or less, the equivalent circle diameter of the maximum pore remaining at the 1 / 2 position of the steel sheet is 200 [mu] m or less, the sheet thickness is greater than 100 mm, and the thickness of the steel sheet is greater than 100 mm. The yield strength at a position 1 / 2 of the sheet thickness is 390 MPa or more, the Charpy fracture transition temperature at a position 1 / 2 of the sheet thickness is vTrs < =-100 DEG C, and the value of Kca (-10 DEG C) is 8400 N / mm3 / 2 or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a high-strength, ultra-thick steel plate having a thickness of more than 100 mm and excellent brittle crack propagation arrest characteristics, which is used in large structures such as ships, marine structures, cryogenic storage tanks, building structures and civil engineering structures, and a method for manufacturing the same. Background Art

[0002] Large structures such as ships, marine structures, cryogenic storage tanks, building structures, and civil engineering structures have a great impact on the social economy and the environment when accidents accompanied by brittle fracture occur. Therefore, large structures are always required to improve safety. For steel materials used in large structures, high levels of toughness and strength at operating temperature and brittle crack propagation stopping properties (crack arrest performance) are required to prevent brittle crack propagation.

[0003] Container ships and bulk carriers are not equipped with a general deck, but the cargo is loaded on the hatch cover. They travel on the ocean while bearing the waves that apply a large load. Therefore, they are repeatedly subjected to large bending stresses due to structural and operational reasons. Therefore, high-strength and thick-walled steel plates that can withstand the bending stress are usually used for the hull outer plate. In recent years, with the enlargement of the hull, the high-strength and thick-walled steel plates used have further developed.

[0004] Generally, the higher the strength or the thicker the wall thickness of a steel plate, the worse the brittle crack propagation arrest property. Therefore, when the steel plates used in container ships and the like in recent years have high strength and thick wall thickness, it is difficult to satisfy the required brittle crack propagation arrest property.

[0005] As a method for improving the brittle crack propagation arrest characteristics of steel materials, it is known in the past to increase the Ni content in steel. For example, in liquefied natural gas (LNG) storage tanks that require brittle crack propagation arrest characteristics at extremely low temperatures, 9% Ni steel is used on a commercial scale. However, the increase in the amount of Ni in the steel has to significantly increase the manufacturing cost, so it is difficult to apply it to uses other than LNG storage tanks.

[0006] On the other hand, for relatively thin steel materials with a thickness of less than 50 mm, such as those used in ships and pipelines, which cannot withstand extremely low temperatures like LNG, the TMCP (Thermo-Mechanical Control Process) method is used to achieve fine graining and improve low-temperature toughness. This can provide excellent brittle crack propagation arrest properties.

[0007] For example, Patent Document 1 discloses a technology in which the microstructure is a mixed structure of ferrite and bainite or a mixed structure of ferrite, pearlite and bainite, and the toughness is improved by controlling the average grain size at the center of the plate thickness to 5 to 20 μm, thereby improving the brittle crack propagation arrest characteristics.

[0008] In order to improve the brittle crack propagation arrest property without increasing the alloy cost, Patent Documents 2 and 3, for example, disclose technologies for making the structure of the surface layer of a steel material ultrafine.

[0009] Patent Document 2 focuses on the effect of the shear lip (i.e., plastic deformation area) generated in the surface of the steel material when the brittle crack propagates, which is effective in improving the brittle crack propagation stopping characteristics. Patent Document 2 discloses that by refining the grains in the shear lip part, the propagation energy of the propagating brittle crack is absorbed by the grains. In addition, Patent Document 2 discloses that as a manufacturing method, the surface part is cooled to a temperature below the Ar3 transformation point by controlled cooling after hot rolling, and then the controlled cooling is stopped, and the surface part is heated back to a temperature above the Ar3 transformation point, and this process is repeated more than once. Patent Document 2 discloses that by applying pressure to the steel material in this process, it is repeatedly transformed or recrystallized by processing, thereby generating an ultrafine ferrite structure or bainite structure in the surface part.

[0010] Patent Document 3 discloses that, in order to improve the brittle crack propagation arrest characteristics in a steel material having a microstructure mainly composed of ferrite-pearlite, both surface portions of the steel material are composed of a layer of a ferrite structure having ferrite grains having an equivalent circle grain size of 5 μm or less and an aspect ratio of 2 or more, accounting for 50% or more of the area, and that the fluctuation of the ferrite grain size is suppressed. As a method for suppressing the fluctuation, Patent Document 3 discloses that the local recrystallization phenomenon is suppressed by setting the maximum reduction rate per pass in the finishing rolling to 12% or less.

[0011] In addition, a method of improving the brittle crack propagation arrest property by applying reduction to the transformed ferrite to develop the texture during controlled rolling is also known. For example, the techniques of Patent Documents 4 and 5 can be cited.

[0012] In Patent Document 4, the texture is controlled as follows: the average equivalent circle diameter of the effective grains is 25 μm or less in the surface part of the thick steel plate, and is 35 μm or less in the center part of the plate thickness, and the texture strength ratio relative to the rolling surface and the rolling direction satisfies I{001}<110>+I{112}<110>+I{332}<113>>5, I{110}<001>+I{110}<110>+I{001}<010>≤3 in the surface part of the thick steel plate, and satisfies I{001}<110>+I{112}<110>+I{332}<113>≥3.5 in the center part of the plate thickness. Thus, Patent Document 4 discloses a technology for improving the brittle crack propagation arrest characteristics.

[0013] Patent Document 5 controls the steel plate in the following manner: the steel plate is divided into three layers: a surface and back layer portion from the front and back sides of the steel plate to 25% in the plate thickness direction, and a center portion of the plate thickness other than the surface and back layers. In the surface and back layers, a texture having a (100) X-ray surface intensity ratio of 1.5 or more and less than 2.0 parallel to the rolling surface is present in a region of 5% or more and 25% or less of the plate thickness, and a texture having a (111) or / and (211) X-ray surface intensity ratio of 2.0 or more parallel to the rolling surface is present in the center portion of the plate thickness. Thus, Patent Document 5 discloses a technique for improving the brittle crack propagation arrest characteristics.

[0014] Prior art literature

[0015] Patent Literature

[0016] Patent Document 1: International Publication No. 2011 / 96456

[0017] Patent Document 2: Japanese Patent Application Publication No. 2002-256375

[0018] Patent Document 3: Japanese Patent Application Publication No. 2011-184754

[0019] Patent Document 4: Japanese Patent Application Publication No. 2012-172258

[0020] Patent Document 5: Japanese Patent Application Publication No. 2008-169467 Summary of the invention

[0021] Problems to be solved by the invention

[0022] However, in the techniques described in Patent Documents 2 and 3, only the surface layer of the steel is temporarily cooled and then reheated, and then processed during the reheating to obtain a specific structure. Therefore, it is not easy to control in actual production scale, and there is a problem of heavy load on rolling equipment and cooling equipment.

[0023] In addition, in the technologies described in Patent Documents 1 to 5, if the manufacturing conditions and the disclosed experimental data are all taken into consideration, the steel plates and steel materials with a plate thickness of about 80 mm are the main objects, and it is unclear whether the specified characteristics can be obtained when each technology is applied to an extremely thick steel plate of more than 100 mm. In addition, it is also unclear whether the crack propagation stopping characteristics in the plate thickness direction required for the hull structure can be obtained. However, it can be expected that in an extremely thick steel plate of more than 100 mm, the characteristics required to stop crack propagation become higher than those in a steel plate of about 80 mm thickness.

[0024] Furthermore, in order to improve the brittle crack propagation arrest characteristics while maintaining the rigidity of the hull, even extremely thick steel plates greater than 100 mm are required to have both high strength and excellent toughness.

[0025] The present invention has been made in view of the above problems, and an object of the present invention is to provide a high-strength ultra-thick steel plate having excellent toughness and brittle crack propagation arrest characteristics even when the plate thickness exceeds 100 mm, and a method for producing the same.

[0026] Here, "high strength" in the present invention means that the yield strength (YS) of the high-strength ultra-thick steel plate at 1 / 2 of the plate thickness is 390 MPa or more. "Excellent toughness" in the present invention means that the Charpy fracture transition temperature of the high-strength ultra-thick steel plate at 1 / 2 of the plate thickness is vTrs≤-100°C. "Excellent brittle crack propagation stopping characteristics (crack arrest characteristics)" in the present invention means the Kca value at -10°C (hereinafter also recorded as Kca (-10°C) value (N / mm 3 / 2 )) is 8400N / mm 3 / 2 above.

[0027] In addition, the yield strength, vTrs and Kca value can be measured by the method described in the Examples mentioned later.

[0028] Methods used to solve problems

[0029] In order to solve the above problems, the present inventors have repeatedly conducted intensive research on a high-strength ultra-thick steel plate that has excellent toughness and brittle crack propagation arrest characteristics while ensuring strength even when the plate thickness exceeds 100 mm, and a method for stably obtaining the steel plate. As a result, the following findings were obtained.

[0030] Specifically, in order to achieve high strength of an ultra-thick steel plate with a thickness greater than 100 mm, it is effective to control the carbon equivalent (Ceq) to 0.480 mass % or more, thereby increasing the strength by making the steel structure at the 1 / 2 thickness position bainite throughout the entire surface, thereby achieving high strength.

[0031] In addition, in order to achieve the excellent toughness of the above-mentioned ultra-thick steel plate, it is effective to control the steel structure at the 1 / 2 position of the plate thickness so that the grains of bainite surrounded by grain boundaries with an orientation difference of 15° or more are 20μm or less, and to control the equivalent circle diameter of the largest pores remaining in the center of the steel plate to 200μm or less. As a result, the toughness is improved by the effect of grain refinement, and the Charpy toughness at the 1 / 2 position of the plate thickness, where the characteristics are the lowest, reaches vTrs≤-100℃.

[0032] In addition, in order to achieve the excellent brittle crack propagation arrest characteristics of the above-mentioned ultra-thick steel plate, it is effective to have excellent toughness and form a texture with an X-ray intensity of 1.60 or more on the (211) plane in the rolled surface at the 1 / 2 thickness position. In this way, the brittle crack is suppressed from advancing linearly and the value of Kca (-10°C) (N / mm 3 / 2 )≥8400N / mm 3 / 2 .

[0033] Furthermore, in order to obtain the above toughness, in the hot rolling process, it is effective to control the cumulative reduction rate when the temperature at the 1 / 2 position of the plate thickness is within the austenite non-recrystallization temperature range to 50.0% or more, and to control the reduction ratio, which represents the ratio of the thickness of the steel billet to the plate thickness of the final product, to 3.25 or more. As a result, even an extremely thick steel plate greater than 100 mm will not be affected by the plate thickness, and sufficient rolling stress can be applied to the 1 / 2 position of the plate thickness. As a result, the average grain size of the bainite grains can be controlled to the above-mentioned average grain size, and the pores at the 1 / 2 position of the plate thickness of the steel plate, which is the starting point of fracture, can be pressed, thereby achieving excellent toughness.

[0034] In addition, in order to obtain the above-mentioned brittle crack propagation stop characteristics, in the hot rolling process, the cumulative reduction rate within the above-mentioned austenite non-recrystallization temperature range is controlled to be above 50.0%, and the above-mentioned reduction ratio is controlled to be above 3.25, and the rolling end temperature at the 1 / 2 position of the plate thickness is controlled to be above the Ar3 point. Through this control, the grains of the steel structure at the 1 / 2 position of the plate thickness are made fine, and it is effective to control the texture at the 1 / 2 position of the plate thickness. As a result, while achieving excellent low-temperature toughness, the austenite can be extended along the rolling direction, and the bainite phase transformation texture can be uniformly developed along a specific orientation. As a result, a texture with an X-ray intensity of 1.60 or more on the (211) plane in the rolling surface at the 1 / 2 position of the plate thickness can be obtained.

[0035] The present invention has been completed by further studying the above findings, and the gist of the present invention is as follows.

[0036] [1] A high-strength, extra-thick steel plate having a composition comprising, in mass %, 0.040 to 0.150% C, 0.02 to 0.50% Si, 1.00 to 2.50% Mn, 0.020% or less P, 0.010% or less S, 0.010% or less Al, 0.010% to 0.100% N, and 0.0010 to 0.0100% O, wherein Ceq defined by formula (1) is 0.480 to 0.560%, and the balance is Fe and unavoidable impurities,

[0037] The texture has an X-ray intensity ratio of the (211) plane in the rolled surface at a position of 1 / 2 of the plate thickness of 1.60 or more,

[0038] and having a steel structure at a position of 1 / 2 of the plate thickness as described below, wherein the steel structure at the position of 1 / 2 of the plate thickness is a mixed structure consisting of 80 to 100% of a bainite phase and 0 to 20% of a ferrite phase in terms of area fraction, the average grain size of bainite grains surrounded by grain boundaries with an orientation difference of 15° or more is 20 μm or less, and the equivalent circle diameter of the largest pore remaining at the position of 1 / 2 of the plate thickness is 200 μm or less,

[0039] The thickness of the high-strength extra-thick steel plate is greater than 100 mm.

[0040] The yield strength at the half thickness position is 390 MPa or more, the Charpy fracture transition temperature at the half thickness position is vTrs≤-100℃, and the Kca (-10℃) value is 8400N / mm 3 / 2 above,

[0041] Ceq=C+Mn / 6+Cu / 15+Ni / 15+Cr / 5+Mo / 5+V / 5…(1)

[0042] Here, C, Mn, Cu, Ni, Cr, Mo, and V in formula (1) represent the content (mass %) of each element, and the content of an element not contained is set to 0.

[0043] [2] The high-strength ultra-thick steel plate according to [1], further comprising, in addition to the above-mentioned component composition, one or two selected from the following Group A and Group B in terms of mass %.

[0044] Group A: one or more selected from the group consisting of Ti: 0.030% or less, Nb: 0.050% or less, Cu: 2.00% or less, Ni: 2.50% or less, and Cr: 2.00% or less

[0045] Group B: one or more selected from the group consisting of Mo: 0.50% or less, V: 0.50% or less, W: 0.50% or less, Co: 0.50% or less, B: 0.0100% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, and REM: 0.0200% or less

[0046] [3] The high-strength ultra-thick steel plate according to [1] or [2], wherein:

[0047] In the above texture, the X-ray intensity ratio of the (110) plane in the rolled surface at the position of 1 / 4 of the plate thickness is 0.90 or more.

[0048] The steel structure at the 1 / 4 thickness position is a mixed structure composed of 80 to 100% of a bainite phase and 0 to 20% of a ferrite phase in terms of area fraction, and the average grain size of bainite grains surrounded by grain boundaries with an orientation difference of 15° or more is 20 μm or less.

[0049] [4] A method for producing a high-strength and ultra-thick steel plate, which is the method for producing a high-strength and ultra-thick steel plate according to any one of [1] to [3], wherein:

[0050] The steel material having the above composition is heated to a heating temperature of 1000 to 1200°C.

[0051] Next, hot rolling is carried out under the conditions that the rolling start temperature at the position of 1 / 2 thickness is (Ar3 point + 100) ° C or more, the cumulative reduction rate when the temperature at the position of 1 / 2 thickness is within the austenite recrystallization temperature range is 5.0% or more, the cumulative reduction rate when the temperature at the position of 1 / 2 thickness is within the austenite non-recrystallization temperature range is 50.0% or more, and the rolling end temperature at the position of 1 / 2 thickness is Ar3 point or more, and the thickness of the steel billet is 350 mm or more, and the reduction ratio representing the ratio of the thickness of the steel billet to the thickness of the final product is 3.25 or more and less than 4.00.

[0052] Next, cooling is carried out under the conditions that the cooling start temperature at the 1 / 2 thickness position is above the Ar3 point, the temperature at the 1 / 2 thickness position is in the temperature range of 700 to 500°C, the average cooling rate is above 2.0°C / s, and the cooling stop temperature at the 1 / 2 thickness position is below 500°C.

[0053] [5] A method for manufacturing a high-strength ultra-thick steel plate according to [4], wherein the hot rolling is further carried out under the conditions that the average reduction rate / pass is 3.5% or more when the temperature at the half-thickness position is within the austenite recrystallization temperature range and the rolling end temperature at the quarter-thickness position is above the Ar3 point.

[0054] Effects of the Invention

[0055] According to the present invention, since it has the steel structure at the 1 / 2 position of the plate thickness as described below, it is possible to obtain a steel plate in which the pores at the 1 / 2 position of the plate thickness are fully crimped, and the steel structure at the 1 / 2 position of the plate thickness is a mixed structure composed of a bainite phase and a ferrite phase, and the average grain size of the above-mentioned bainite grains is less than 20μm, and the equivalent circle diameter of the largest pore remaining in the center of the steel plate is less than 200μm. At the same time, since it has the above-mentioned texture at the 1 / 2 position of the plate thickness, it is possible to hinder the brittle crack from advancing in a straight line. Therefore, the high-strength ultra-thick steel plate of the present invention has excellent toughness and brittle crack propagation stopping characteristics even if the plate thickness is greater than 100mm. In addition, according to the manufacturing method of the present invention, a high-strength ultra-thick steel plate with the above-mentioned characteristics can be manufactured by optimizing the rolling conditions.

[0056] For example, by applying the high-strength and ultra-thick steel plate of the present invention to a deck member joined to a hatch side coaming in a strong deck structure of a container ship or bulk carrier in the shipbuilding field, it helps to improve the safety of the ship. Therefore, the present invention is extremely useful in industry. DETAILED DESCRIPTION

[0057] Hereinafter, embodiments of the present invention will be described. However, the present invention is not limited to the following embodiments.

[0058] First, the reason why the chemical composition of the high-strength ultra-thick steel plate is limited in the present invention is described. In this specification, "%" about the chemical composition means "mass %" unless otherwise specified.

[0059] C: 0.040~0.150%

[0060] C is an element that has the effect of increasing the hardenability of steel and is necessary to achieve the desired strength. In the present invention, in order to obtain the above-mentioned effect, the C content is set to 0.040% or more. On the other hand, when the C content is greater than 0.150%, not only the weldability is deteriorated, but also the toughness is adversely affected. Therefore, the C content is set to the range of 0.040 to 0.150%. It should be noted that, with respect to the lower limit, the preferred C content is 0.050% or more, more preferably 0.055% or more. In addition, with respect to the upper limit, the preferred C content is 0.100% or less, more preferably 0.090% or less.

[0061] Si: 0.02~0.50%

[0062] Si is a necessary component for deoxidation, etc. In addition, Si is an element that has the effect of increasing the hardenability of steel by inhibiting the formation of coarse carbides. In order to achieve the desired strength, more than 0.02% Si is contained. On the other hand, when the Si content is greater than 0.50%, not only the surface properties of the steel are damaged, but also the toughness is extremely deteriorated. Therefore, the Si content is in the range of 0.02 to 0.50%. It should be noted that, with respect to the lower limit, the preferred Si content is more than 0.050%, and more preferably more than 0.10%. In addition, with respect to the upper limit, the preferred Si content is less than 0.40%, and more preferably less than 0.30%.

[0063] Mn: 1.00~2.50%

[0064] Mn is an element having an effect of increasing the hardenability of steel, and is necessary for exerting the desired intensity. In order to obtain the above-mentioned effect, the Mn content is made to be more than 1.00%. On the other hand, when the Mn content is high, the strength is excessively increased, so the toughness is reduced, and the alloy cost is excessively increased. From these viewpoints, the Mn content is below 2.50%. It should be noted that, about the lower limit, the preferred Mn content is more than 1.50%, more preferably more than 1.65%. In addition, about the upper limit, the preferred Mn content is below 2.35%, more preferably below 2.15%.

[0065] P: 0.020% or less, S: 0.010% or less

[0066] P and S are inevitable impurities in steel. When these contents increase, toughness deteriorates. In extremely thick steel plates with a plate thickness greater than 100 mm, in order to maintain good toughness, the P content is suppressed to less than 0.020%, and the S content is suppressed to less than 0.010%. It should be noted that the P content is preferably less than 0.012%, more preferably less than 0.006%. The S content is preferably less than 0.006%, more preferably less than 0.002%.

[0067] It should be noted that there is no particular lower limit on the P content and the S content. However, excessive reduction of P and S leads to an increase in manufacturing costs, so the P content and the S content are preferably P: 0.0005% or more, S: 0.0005% or more, respectively. More preferably, P: 0.002% or more, S: 0.001% or more.

[0068] Al: 0.010~0.100%

[0069] Al is an element that acts as a deoxidizer. In order to obtain this effect, the Al content needs to be 0.010% or more. On the other hand, when the Al content is greater than 0.100%, the toughness decreases, and when welding is performed, the toughness of the weld metal portion decreases. Therefore, the Al content is in the range of 0.010 to 0.100%. It should be noted that, with respect to the lower limit, the preferred Al content is 0.020% or more, and more preferably 0.030% or more. In addition, with respect to the upper limit, the preferred Al content is 0.070% or less, and more preferably 0.040% or less.

[0070] N: 0.0010~0.0100%

[0071] N combines with Al in steel to adjust the grain size during rolling and strengthen the steel. In order to achieve this effect, the N content needs to be 0.0010% or more. In addition, when the N content is greater than 0.0100%, the toughness deteriorates. Therefore, the N content is in the range of 0.0010 to 0.0100%. It should be noted that, with respect to the lower limit, the preferred N content is 0.0020% or more, and more preferably 0.0025% or more. In addition, with respect to the upper limit, the preferred N content is 0.0070% or less, and more preferably 0.0055% or less.

[0072] O: 0.0100% or less

[0073] O (oxygen) is an element contained as an inevitable impurity, and its content is specified because it is an element that should be reduced. O forms oxides and becomes the starting point of brittle fracture, thus bringing about adverse effects such as reduced toughness and the subsequent reduction of brittle crack propagation stop characteristics. Therefore, the O content is limited to less than 0.0100%. The O content is preferably less than 0.0050%, more preferably less than 0.0030%. On the other hand, the lower limit of the O content is not particularly limited and can be 0%. Generally, O is an element that is inevitably contained in steel as an impurity, so it can be greater than 0% in industry. In addition, excessive reduction of O will lead to a surge in refining costs, so from the perspective of cost, the O content is preferably more than 0.0009%, more preferably more than 0.0020%.

[0074] In the present invention, each element is set within the above range and is contained so that the Ceq (carbon equivalent) (%) defined by the formula (1) satisfies the following range.

[0075] Ceq=C+Mn / 6+Cu / 15+Ni / 15+Cr / 5+Mo / 5+V / 5…(1)

[0076] Here, C, Mn, Cu, Ni, Cr, Mo, and V in formula (1) represent the content (mass %) of each element, and the content of an element not contained is set to 0.

[0077] Ceq: 0.480~0.560%

[0078] In order to improve the hardenability of the ultra-thick steel plate of the present invention and achieve high strength and an improvement in the brittle crack propagation stop characteristics associated with the development of the texture, the value of Ceq represented by formula (1) is adjusted to be above 0.480%. As a result, the hardenability of the steel plate increases, and even at the 1 / 2 position of the plate thickness where the cooling rate is the smallest, the steel structure becomes bainite on the entire surface, thereby improving the strength. On the other hand, when the value of Ceq is greater than 0.560%, the hardenability becomes excessive, the strength of the matrix structure increases excessively, and the amount of MA (martensite) generated, which is the starting point of brittle fracture, increases. As a result, the weldability and toughness of the base material (steel plate) cannot be ensured. Therefore, Ceq is set to be below 0.560%. The value of Ceq is preferably above 0.490%, and more preferably above 0.500%. In addition, the value of Ceq is preferably below 0.540%, and more preferably below 0.530%.

[0079] The above is the basic component composition of the present invention, and the balance is Fe and inevitable impurities.

[0080] By having this basic component composition and satisfying the above-mentioned formula (1), the high-strength ultra-thick steel plate of the present invention can obtain target properties.

[0081] In the present invention, in order to further improve the characteristics, in addition to the basic component composition, one or two groups selected from the group A and group B described later may be contained as needed. It should be noted that each component of Ti, Nb, Cu, Ni, Cr, Mo, V, W, Co, B, Ca, Mg, and REM may be contained as needed, so these components may be 0%.

[0082] Group A: one or more selected from the group consisting of Ti: 0.030% or less, Nb: 0.050% or less, Cu: 2.00% or less, Ni: 2.50% or less, and Cr: 2.00% or less

[0083] Ti: 0.030% or less

[0084] Ti forms nitrides, carbides or carbonitrides by containing a small amount, which has the effect of refining the grains and improving the toughness of the base material. In order to obtain this effect, it is preferred that the Ti content is 0.005% or more. On the other hand, when the Ti content is greater than 0.030%, there is a case where the toughness of the base material and the weld heat affected zone is reduced. Therefore, when Ti is contained, the Ti content is preferably 0.030% or less, and more preferably 0.025% or less. The Ti content is more preferably 0.010% or more.

[0085] Nb: 0.050% or less

[0086] Nb has the effect of increasing the hardenability of steel and expanding the non-recrystallization temperature region in rolling (hot rolling) in the austenite region. In order to obtain this effect, it is preferred that the Nb content is 0.005% or more. On the other hand, when the Nb content is greater than 0.050%, coarse NbC precipitates, which may lead to a decrease in toughness. Therefore, when containing Nb, the Nb content is preferably 0.050% or less, more preferably 0.040% or less. The Nb content is more preferably 0.010% or more.

[0087] Cu: 2.00% or less

[0088] Cu is an element that improves the hardenability of steel. Cu directly contributes to the strength improvement after rolling. At the same time, in order to improve the functions such as toughness, high temperature strength and weather resistance, Cu can be contained. In order to obtain the above-mentioned effect produced by this element, it is preferred that the Cu content is more than 0.01%. On the other hand, when the Cu content is greater than 2.00%, it causes the deterioration of weldability and toughness and the rise of alloy cost. Therefore, when containing Cu, the Cu content is preferably less than 2.00%, more preferably less than 1.00%. The Cu content is more preferably more than 0.05%, and further preferably more than 0.10%.

[0089] Ni: 2.50% or less

[0090] Ni is an element that improves the hardenability of steel. Ni directly contributes to the strength improvement after rolling. At the same time, in order to improve the functions such as toughness, high temperature strength and weather resistance, Ni can be contained. In order to obtain the above-mentioned effect produced by this element, it is preferred that the Ni content is more than 0.01%. On the other hand, when the Ni content is greater than 2.50%, it causes the deterioration of weldability and toughness and the rise of alloy cost. Therefore, when containing Ni, the Ni content is preferably less than 2.50%, more preferably less than 2.00%. The Ni content is more preferably more than 0.10%.

[0091] Cr: 2.00% or less

[0092] Cr is an element that improves the hardenability of steel. Cr directly contributes to the improvement of strength after rolling. At the same time, Cr can be contained in order to improve functions such as toughness, high temperature strength and weather resistance. In order to obtain the above-mentioned effects produced by this element, it is preferred that the Cr content is 0.01% or more. On the other hand, when the Cr content is greater than 2.00%, it leads to deterioration of weldability and toughness and an increase in alloy cost. Therefore, when Cr is contained, the Cr content is preferably less than 2.00%, and more preferably less than 1.00%. The Cr content is more preferably more than 0.05%, and further preferably more than 0.10%.

[0093] Group B: one or more selected from the group consisting of Mo: 0.50% or less, V: 0.50% or less, W: 0.50% or less, Co: 0.50% or less, B: 0.0100% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, and REM: 0.0200% or less

[0094] Mo: 0.50% or less

[0095] Mo is an element that improves the hardenability of steel. Mo directly contributes to the strength improvement after rolling. At the same time, in order to improve the functions such as toughness, high temperature strength and weather resistance, Mo can be contained. In order to obtain the above-mentioned effect produced by this element, it is preferred that the Mo content is 0.01% or more. On the other hand, when the Mo content is greater than 0.50%, it causes the deterioration of weldability and toughness and the increase of alloy cost. Therefore, when containing Mo, the Mo content is preferably 0.50% or less, more preferably 0.30% or less. The Mo content is more preferably 0.03% or more.

[0096] V: 0.50% or less

[0097] V is an element that improves the strength of steel by precipitation strengthening in the form of V (CN). This effect is exerted by making the V content 0.001% or more. However, when the V content is greater than 0.50%, there is a situation where toughness decreases. Therefore, in the case of containing V, the V content is preferably 0.50% or less, more preferably 0.30% or less. The V content is more preferably 0.005% or more, and further preferably 0.010% or more.

[0098] W: 0.50% or less

[0099] W is an element that has the effect of increasing the strength of the steel sheet. In order to obtain this effect, the W content is preferably 0.001% or more. On the other hand, when the W content is greater than 0.50%, the weldability is deteriorated and the alloy cost increases. Therefore, when W is contained, the W content is preferably 0.50% or less, and more preferably 0.30% or less. The W content is more preferably 0.005% or more.

[0100] Co: 0.50% or less

[0101] Co is an element that has the effect of increasing the strength of the steel sheet. In order to obtain this effect, the Co content is preferably 0.001% or more. On the other hand, when the Co content is greater than 0.50%, the weldability is deteriorated and the alloy cost is increased. Therefore, when Co is contained, the Co content is preferably 0.50% or less, more preferably 0.40% or less, and further preferably 0.30% or less. The Co content is more preferably 0.005% or more.

[0102] B: 0.0100% or less

[0103] B is an element that improves the hardenability of steel in trace amounts. However, when B is contained in an amount greater than 0.0100%, the toughness of the weld is reduced. Therefore, when B is contained, the B content is preferably 0.0100% or less, more preferably 0.0030% or less. In order to increase the strength of the steel plate, the B content is preferably 0.0001% or more, more preferably 0.0005% or more, and further preferably 0.0010% or more.

[0104] Ca: 0.0100% or less

[0105] Ca refines the structure of the weld heat affected zone and improves toughness. In order to obtain this effect, when Ca is contained, the Ca content is preferably 0.0005% or more, and more preferably 0.0020% or more. On the other hand, when the Ca content exceeds 0.0100%, coarse inclusions are formed, which deteriorates toughness. Therefore, when Ca is contained, the Ca content is preferably 0.0100% or less, and more preferably 0.050% or less.

[0106] Mg: 0.0100% or less

[0107] Mg, like Ca, refines the structure of the weld heat affected zone and improves toughness. In order to obtain this effect, when Mg is contained, the Mg content is preferably 0.0005% or more, and more preferably 0.0020% or more. On the other hand, when the Mg content exceeds 0.0100%, coarse inclusions are formed, which deteriorates toughness. Therefore, when Mg is contained, the Mg content is preferably 0.0100% or less, and more preferably 0.0050% or less.

[0108] REM: 0.0200% or less

[0109] REM (rare earth metal) refines the structure of the weld heat affected zone and improves toughness, similarly to Ca. In order to obtain this effect, when REM is contained, the content of REM is preferably 0.0005% or more, more preferably 0.0015% or more, and further preferably 0.0100% or more. On the other hand, when the REM content exceeds 0.0200%, coarse inclusions are formed, deteriorating toughness. Therefore, when REM is contained, the REM content is preferably 0.0200% or less.

[0110] <Texture>

[0111] X-ray intensity ratio of (211) plane in the rolled surface at the half thickness position: 1.60 or more

[0112] For extremely thick steel plates with a thickness greater than 100 mm, in order to improve the brittle crack propagation stopping characteristics, it is necessary to make the X-ray intensity ratio of the (211) plane in the rolled surface at the position of 1 / 2 of the plate thickness greater than 1.60 or more. When the X-ray intensity ratio of the (211) plane is less than 1.60, the brittle crack tends to progress in a straight line, and as a result, the brittle crack propagation stopping characteristics of the plate thickness are reduced. Therefore, the X-ray intensity ratio of the (211) plane in the rolled surface at the position of 1 / 2 of the plate thickness is greater than 1.60. In order to further improve the brittle crack propagation stopping characteristics, the X-ray intensity ratio of the above-mentioned (211) plane is preferably greater than 1.70, and more preferably greater than 1.80.

[0113] It should be noted that the upper limit of the X-ray intensity ratio of the (211) plane is not particularly specified. From the viewpoint of rolling efficiency and manufacturing load, the X-ray intensity ratio of the (211) plane is preferably 2.50 or less, and more preferably 2.30 or less.

[0114] Here, the X-ray intensity ratio of the (211) plane refers to a numerical value indicating the degree of aggregation of the (211) crystal plane of the target material (i.e., the high-strength ultra-thick steel plate). As described in the examples described below, the X-ray intensity ratio of the (211) plane is the X-ray diffraction intensity (I (211) ) and the X-ray diffraction intensity of the (211) reflection of a random standard sample without texture (I 0(211) ) ratio (i.e., I (211) / I 0(211) ) to calculate.

[0115] <Steel structure at 1 / 2 plate thickness>

[0116] In the present invention, the steel structure at the 1 / 2 thickness position is a mixed structure composed of 80 to 100% of a bainite phase and 0 to 20% of a ferrite phase in terms of area fraction, the average grain size of bainite grains surrounded by grain boundaries with an orientation difference of 15° or more is less than 20 μm, and the equivalent circle diameter of the largest pore remaining at the 1 / 2 thickness position (center of the plate thickness) is less than 200 μm.

[0117] [Area fraction of bainite phase at 1 / 2 thickness: 80-100%]

[0118] In the high-strength ultra-thick steel plate of the present invention, the area fraction of the bainite phase at the 1 / 2 position of the plate thickness needs to be 80-100%. When the area fraction of the bainite phase is less than 80%, the fraction of the hard structure is reduced, and the texture of the (211) plane is not fully developed, so the strength and brittle crack propagation stop characteristics are reduced. Therefore, the area fraction of the bainite phase at the 1 / 2 position of the plate thickness is made to be 80% or more. In order to further improve the strength and brittle crack propagation stop characteristics, the above-mentioned area fraction is preferably 85% or more, and more preferably 90% or more.

[0119] [Area fraction of ferrite phase at 1 / 2 thickness position: 0 to 20%]

[0120] In the high-strength ultra-thick steel plate of the present invention, the area fraction of the ferrite phase at the 1 / 2 position of the plate thickness needs to be 0 to 20%. When the area fraction of the ferrite phase is greater than 20%, the fraction of the hard structure decreases, and the texture of the (211) plane is not fully developed, so the strength and brittle crack propagation stop characteristics are reduced. Therefore, the area fraction of the ferrite phase at the 1 / 2 position of the plate thickness is made less than 20%. In order to further improve the strength and brittle crack propagation stop characteristics, the above-mentioned area fraction is preferably less than 15%, and more preferably less than 10%.

[0121] [Average grain size of bainite at the half thickness position: 20 μm or less]

[0122] In the high-strength ultra-thick steel plate of the present invention, the average grain size of the bainite grains at the 1 / 2 position of the plate thickness needs to be 20 μm or less. When the average grain size is greater than 20 μm, as the grain size coarsens, the fracture unit of the cleavage fracture of the grains becomes larger, so the toughness and brittle crack propagation stop characteristics are reduced. Therefore, the average grain size of the grains at the 1 / 2 position of the plate thickness is set to 20 μm or less. In order to further improve the toughness and brittle crack propagation stop characteristics, the above average grain size is preferably 19 μm or less, and more preferably 18 μm or less.

[0123] It should be noted that the lower limit of the average grain size is not particularly specified. From the viewpoint of rolling efficiency, the average grain size is preferably 5 μm or more, and more preferably 10 μm or more.

[0124] [Equivalent circle diameter of pores remaining at 1 / 2 of plate thickness: 200 μm or less]

[0125] In the high-strength ultra-thick steel plate of the present invention, the equivalent circular diameter of the largest pore remaining at the position of 1 / 2 of the plate thickness needs to be 200μm or less. When the equivalent circular diameter of the largest pore is greater than 200μm, the pore becomes the starting point of fracture and the toughness is significantly reduced. Therefore, the equivalent circular diameter of the largest remaining pore at the position of 1 / 2 of the plate thickness is less than 200μm. In order to further improve the toughness, the above-mentioned equivalent circular diameter is preferably less than 150μm, and more preferably less than 100μm. It should be noted that the lower limit of the above-mentioned equivalent circular diameter is not specifically specified. From the viewpoint of rolling efficiency, the above-mentioned equivalent circular diameter is preferably greater than 25μm, more preferably greater than 50μm, and further preferably greater than 70μm.

[0126] It should be noted that in the present invention, in addition to the above-mentioned steel structure and texture, the following configuration may be further provided.

[0127] <Steel structure at 1 / 4 of plate thickness> (optimal conditions)

[0128] In the present invention, the steel structure at the 1 / 4 thickness position is preferably a mixed structure consisting of 80 to 100% of a bainite phase and 0 to 20% of a ferrite phase in terms of area fraction. In addition, the average grain size of bainite grains surrounded by grain boundaries with an orientation difference of 15° or more is preferably 20 μm or less.

[0129] [Area fraction of bainite phase at 1 / 4 of plate thickness: 80-100%]

[0130] In the high-strength ultra-thick steel plate of the present invention, the area fraction of the bainite phase at the 1 / 4 position of the plate thickness is preferably 80 to 100%. When the area fraction of the bainite phase is less than 80%, the fraction of the hard structure is reduced, and the texture of the (110) plane is not fully developed, so the strength and brittle crack propagation stop characteristics are reduced. Therefore, the area fraction of the bainite phase at the 1 / 4 position of the plate thickness is preferably 80% or more. In order to further improve the strength and brittle crack propagation stop characteristics, the above-mentioned area fraction is preferably 85% or more, and more preferably 90% or more.

[0131] [Area fraction of ferrite phase at 1 / 4 of plate thickness: 0 to 20%]

[0132] In the high-strength ultra-thick steel plate of the present invention, the area fraction of the ferrite phase at the 1 / 4 position of the plate thickness is preferably 0 to 20%. When the area fraction of the ferrite phase is greater than 20%, the fraction of the hard structure decreases, and the texture of the (110) plane is not fully developed, so the strength and brittle crack propagation stop characteristics are reduced. Therefore, the area fraction of the ferrite phase at the 1 / 4 position of the plate thickness is preferably 20% or less. In order to further improve the strength and brittle crack propagation stop characteristics, the above-mentioned area fraction is preferably 15% or less, and more preferably 10% or less.

[0133] [Average grain size of bainite at 1 / 4 of plate thickness: 20 μm or less]

[0134] In the high-strength ultra-thick steel plate of the present invention, the average grain size of the bainite grains at the 1 / 4 position of the plate thickness is preferably 20 μm or less. When the average grain size is greater than 20 μm, as the grain size coarsens, the fracture unit of the cleavage fracture of the grains becomes larger, so the brittle crack propagation arrest property decreases. Therefore, the average grain size of the bainite grains at the 1 / 4 position of the plate thickness is preferably 20 μm or less. In order to further improve the brittle crack propagation arrest property, the above average grain size is preferably 19 μm or less, and more preferably 16 μm or less.

[0135] It should be noted that the lower limit of the average grain size is not particularly specified. From the viewpoint of rolling efficiency, the average grain size is preferably 5 μm or more, and more preferably 10 μm or more.

[0136] <Texture>(Preferred conditions)

[0137] [X-ray intensity ratio of (110) plane in the rolled surface at the position of 1 / 4 of the plate thickness: 0.90 or more]

[0138] For extremely thick steel plates with a thickness greater than 100 mm, in order to improve the brittle crack propagation stopping characteristics, the X-ray intensity ratio of the (110) plane in the rolled surface at the 1 / 4 position of the plate thickness is preferably greater than 0.90. When the X-ray intensity ratio of the (110) plane is less than 0.90, the orientation difference with the texture at the 1 / 2 position of the plate thickness becomes smaller, the brittle cracks are not dispersed, and they tend to progress in a straight line. As a result, the brittle crack propagation stopping characteristics of the plate thickness are reduced. Therefore, the X-ray intensity ratio of the (110) plane in the rolled surface at the 1 / 4 position of the plate thickness is set to be greater than 0.90. In order to further improve the brittle crack propagation stopping characteristics, the X-ray intensity ratio of the above-mentioned (110) plane is preferably greater than 1.00, and more preferably greater than 1.10.

[0139] It should be noted that the upper limit of the X-ray intensity ratio of the (110) plane is not particularly limited. From the viewpoint of rolling efficiency, the X-ray intensity ratio of the (110) plane is preferably 1.50 or less, and more preferably 1.30 or less.

[0140] Here, the X-ray intensity ratio of the (110) plane refers to a numerical value indicating the degree of aggregation of the (110) crystal plane of the target material (high-strength ultra-thick steel plate). As described in the examples described later, the X-ray intensity ratio of the (110) plane is the X-ray diffraction intensity (I (110) ) and the X-ray diffraction intensity of the (110) reflection of a random standard sample without texture (I 0(110) ) ratio (i.e., I (110) / I 0(110) ) to calculate.

[0141] <Strength>

[0142] Yield strength at 1 / 2 thickness: 390MPa or more

[0143] For the high-strength and extra-thick steel plate of the present invention, the yield strength measured using a JIS 14A tensile test piece of φ14 mm cut from a depth of 1 / 2 of the plate thickness (i.e., the 1 / 2 position of the plate thickness) is 390 MPa or more. Ships such as container ships and bulk carriers generally use high-strength and thick-walled steel plate base materials that can withstand this bending stress, and are not suitable for use when the yield strength is less than 390 MPa.

[0144] <Charpy fracture transition temperature>

[0145] vTrs at 1 / 2 of plate thickness: below -100℃

[0146] For ultra-thick steel plates with a thickness greater than 100 mm, in order to improve the brittle crack propagation arrest characteristics, the vTrs at the 1 / 2 plate thickness position needs to be below -100°C. When the transformation temperature is higher than vTrs: -100°C, the brittle crack propagation arrest characteristics of the plate thickness are reduced. Therefore, the vTrs of the high-strength ultra-thick steel plate of the present invention at the 1 / 2 plate thickness position is set to below -100°C. In order to further improve the brittle crack propagation arrest characteristics, vTrs is preferably below -110°C, and vTrs is more preferably below -120°C. It should be noted that there is no special regulation for the lower limit of vTrs. From the viewpoint of rolling efficiency, the above-mentioned vTrs is preferably above -160°C, and more preferably above -150°C.

[0147] As described in the examples described later, vTrs is evaluated by cutting out a JIS No. 4 impact test piece from a position of 1 / 2 of the plate thickness of a high-strength ultra-thick steel plate and performing a Charpy test.

[0148] <Brittle crack propagation arrest characteristics>

[0149] Kca(-10℃) value: 8400N / mm 3 / 2 above

[0150] For extremely thick steel plates with a thickness greater than 100 mm, in order to prevent the propagation of brittle cracks in the hull, the Kca (-10°C) value needs to be 8400 N / mm 3 / 2 In order to further improve the brittle crack propagation arrest characteristics, it is preferred that the Kca value at -10°C be 9000 N / mm 3 / 2 The above. It should be noted that the upper limit of the Kca value is not particularly specified. From the viewpoint of rolling efficiency, the Kca value at -10°C is preferably 25000 N / mm 3 / 2 Below, more preferably 20000N / mm 3 / 2 the following.

[0151] As described in the examples described later, the Kca value can be evaluated by performing a temperature gradient type standard ESSO test.

[0152] As described above, by adjusting the above-mentioned component composition, controlling the texture and the toughness at a specific position (i.e., refining the steel structure at the position of 1 / 2 of the plate thickness), the high-strength ultra-thick steel plate of the present invention has high strength, high toughness and high (excellent) brittle crack propagation arrest characteristics even when the plate thickness is greater than 100 mm.

[0153] The upper limit of the thickness of the high-strength ultra-thick steel plate of the present invention is not particularly limited, but from the viewpoint of rolling efficiency, the upper limit of the thickness is preferably 180 mm or less.

[0154] Next, a method for producing a high-strength ultra-thick steel plate according to an embodiment of the present invention will be described.

[0155] The high-strength ultra-thick steel plate of the present invention is produced by subjecting a steel material having the above-mentioned component composition to a heating step, a hot rolling step, and a cooling step under specific conditions described below.

[0156] Each step is described in detail below. Unless otherwise specified, the temperature in each step refers to the temperature at the center of the plate thickness of the steel material and the hot-rolled plate (i.e., the position of 1 / 2 of the plate thickness). For example, the temperature distribution in the cross section of the steel plate can be calculated by heat transfer analysis and the result can be corrected by the surface temperature of the steel plate.

[0157] <Heating process>

[0158] First, the steel material having the above-mentioned component composition is heated to a heating temperature of 1000 to 1200°C.

[0159] [Heating temperature of steel material: 1000~1200℃]

[0160] When the heating temperature of the steel raw material is lower than 1000°C, the heating temperature is too low, the deformation resistance becomes high, and the load on the hot rolling mill increases. Therefore, it is difficult to implement the subsequent hot rolling process. Therefore, the above heating temperature is set to be above 1000°C. On the other hand, at a high temperature of more than 1200°C for the heating temperature of the steel raw material, the austenite grains coarsen, and as a result, the toughness decreases, and the desired brittle crack propagation stop characteristics cannot be obtained. In addition, the strength of the steel plate decreases. Moreover, oxidation becomes significant, oxidation loss increases, and the yield may decrease. For such reasons, the above heating temperature is set to be below 1200°C. It should be noted that the above heating temperature is preferably above 1050°C, and more preferably above 1080°C. The above heating temperature is preferably below 1150°C, and more preferably below 1130°C.

[0161] <Hot rolling process>

[0162] Next, the steel raw material heated in the heating process is hot rolled under the conditions that the rolling start temperature at the 1 / 2 position of the plate thickness is above (Ar3 point + 100)°C, the cumulative reduction rate when the temperature at the 1 / 2 position of the plate thickness is within the austenite recrystallization temperature range is 5.0% or more, the cumulative reduction rate when the temperature at the 1 / 2 position of the plate thickness is within the austenite non-recrystallization temperature range is 50.0% or more, and the rolling end temperature at the 1 / 2 position of the plate thickness is above the Ar3 point, and the thickness of the steel billet is above 350 mm, and the reduction ratio representing the ratio of the thickness of the steel billet to the thickness of the final product is 3.25 or more and less than 4.00.

[0163] [Rolling start temperature: (Ar3 point + 100)°C or above]

[0164] When the steel raw material heated in the above-mentioned heating process is hot rolled, if the temperature for starting hot rolling at the position of 1 / 2 of the plate thickness is lower than (Ar3 point + 100) ° C, recrystallization cannot be fully induced in the hot-rolled plate after the hot rolling process. Therefore, the austenite grain size does not become finer and the toughness decreases. As a result, the desired brittle crack propagation stop characteristics cannot be obtained. Therefore, the rolling start temperature is set to above (Ar3 point + 100) ° C. From the viewpoint of ensuring the time for hot rolling in the non-recrystallization region described later, the rolling start temperature is preferably above (Ar3 point + 150) ° C, and more preferably above (Ar3 point + 200) ° C. The upper limit of the rolling start temperature can be based on the heating temperature of the above-mentioned steel raw material. That is, the rolling start temperature is preferably below 1150 ° C, and more preferably below 1130 ° C.

[0165] It should be noted that the Ar3 point (Ar3 transformation point) (°C) can be calculated according to the following formula (3).

[0166] Ar3 point (℃) = 910-273×C-74×Mn-57×Ni-16×Cr-9×Mo-5×Cu…(3)

[0167] Here, in the formula (3), each element symbol represents the content (mass %) of the element in the steel, and an element not contained is set to 0.

[0168] [Cumulative reduction within the austenite recrystallization temperature range: 5.0% or more]

[0169] Hot rolling is performed with a cumulative reduction ratio of 5.0% or more when the temperature at the center of the plate thickness (1 / 2 plate thickness position) is within the austenite recrystallization temperature range. When the cumulative reduction ratio within this temperature range is less than 5.0%, the austenite is not sufficiently refined and the toughness is not improved. As a result, the Charpy fracture transformation temperature at the 1 / 2 plate thickness position: -100°C or less cannot be reached. The cumulative reduction ratio within this temperature range is preferably 10% or more, and more preferably 15% or more.

[0170] The upper limit of the cumulative reduction rate in this temperature range is not particularly limited. Since the above-mentioned effect of improving fine graining is saturated, the cumulative reduction rate in this temperature range is preferably 45% or less, and more preferably 40% or less.

[0171] In the case of the component composition of the present invention, the cumulative reduction ratio in the austenite recrystallization temperature range is preferably set to 5.0% or more in the temperature range of 1100 to 950°C.

[0172] [Cumulative reduction ratio within the austenite non-recrystallization temperature range: 50.0% or more]

[0173] Further, hot rolling is performed with a cumulative reduction ratio of 50.0% or more when the temperature at the center of the plate thickness (the position of 1 / 2 of the plate thickness) is within the austenite non-recrystallization temperature range. By making the cumulative reduction ratio within this temperature range 50.0% or more, the rolling texture developed when rolling the austenite phase transforms from austenite to bainite. At this time, by performing phase transformation along the slip system selected by variant selection, a texture with an X-ray intensity ratio of 1.60 or more in the (211) plane in the rolling surface at the center of the plate thickness can be obtained.

[0174] On the other hand, when the cumulative reduction rate in this temperature range is less than 50%, austenite does not fully extend in the rolling direction, and the nucleation sites during the bainite transformation are reduced, thereby generating coarse bainite and failing to refine the grain size. As a result, the Charpy fracture transformation temperature (vTrs) at the half-thickness position cannot be achieved: -100°C or less. In addition, a texture with a (211) plane aggregation degree of 1.60 or more in the rolled surface at the center of the plate thickness cannot be obtained.

[0175] Therefore, the cumulative reduction ratio in this temperature range is 50.0% or more, preferably 55% or more, and more preferably 60% or more.

[0176] The upper limit of the cumulative reduction ratio in this temperature range is not particularly limited. From the viewpoint of not hindering the rolling efficiency, the cumulative reduction ratio in this temperature range is preferably 75% or less, and more preferably 70% or less.

[0177] In the case of the component composition of the present invention, the cumulative reduction rate in the austenite non-recrystallization temperature range is preferably 50.0% or more in the temperature range of less than 950°C and 700°C or more.

[0178] [Rolling end temperature at 1 / 2 thickness position: Ar3 point or higher]

[0179] The hot rolling process needs to be completed at a temperature above the Ar3 point (°C) at the rolling end temperature at the position of 1 / 2 of the plate thickness. During hot rolling, when the temperature of the steel plate is lower than the Ar3 point (°C), the phase transformation to ferrite begins, and the fraction of bainite that increases the X-ray intensity of the (211) plane decreases, so the X-ray intensity ratio of the (211) plane decreases. As a result, excellent brittle crack propagation arrest characteristics cannot be obtained. Moreover, the lower the temperature, the greater the deformation resistance, which creates a problem of increased load on the hot rolling mill. It should be noted that from the viewpoint of making the cooling start temperature of the subsequent process above the Ar3 point (°C), the rolling end temperature is preferably above (Ar3 point + 10)°C.

[0180] The upper limit of the rolling end temperature is not particularly limited. From the viewpoint of rolling efficiency, the rolling end temperature is preferably (Ar3 point + 60)°C or lower, and more preferably (Ar3 point + 50)°C or lower.

[0181] [Reduction ratio: 3.25 or more and less than 4.00]

[0182] In the present invention, the thickness of the hot rolled sheet after the hot rolling process is important as follows: Specifically, the rolling in the hot rolling process is controlled so that the thickness of the slab is 350 mm or more and the ratio of the slab thickness to the thickness of the final product (reduction ratio) is 3.25 or more.

[0183] When the reduction ratio is less than 3.25, the steel structure is not sufficiently refined, so the toughness is not improved. As a result, the Charpy fracture transition temperature at the 1 / 2 position of the plate thickness cannot be reached: below -100°C. In addition, when the reduction ratio is less than 3.25, the rolling stress applied to the 1 / 2 position of the plate thickness becomes insufficient, and the pores generated inside the steel plate do not deform in the direction of closure. Even at the end of rolling, coarse pores remain and become the starting point of fracture. Therefore, the pores generated inside the steel plate will not be crimped, and the toughness is significantly reduced. The reduction ratio is preferably greater than 3.40, and more preferably greater than 3.50.

[0184] On the other hand, when the reduction ratio is 4.00 or more, the steel structure is excessively fine-grained, the hardenability is reduced, and the area fraction of bainite at the 1 / 2 position of the plate thickness of the ultra-thick steel plate of more than 100 mm with a low cooling rate cannot be increased. As a result, the X-ray intensity ratio of the (211) plane is reduced, and excellent brittle crack propagation arrest characteristics cannot be obtained. In addition, the strength is reduced. Therefore, the reduction ratio needs to be less than 4.00. The reduction ratio is preferably 3.80 or less, and more preferably 3.70 or less.

[0185] In the present invention, the above-mentioned effects can be obtained by hot rolling under the above-mentioned hot rolling conditions. From the viewpoint of more effectively obtaining the effects, it is also effective to further define the following hot rolling conditions.

[0186] Specifically, the average reduction ratio / pass when the temperature at the half-thickness position is within the austenite recrystallization temperature range is 3.5% or more, and the rolling end temperature at the quarter-thickness position is Ar3 point °C or more.

[0187] [Average reduction rate within austenite recrystallization temperature range / pass: 3.5% or more] (optional condition)

[0188] When the temperature at the center of the plate thickness (1 / 2 plate thickness position) is within the austenite recrystallization temperature range, the average reduction rate / pass of hot rolling is 3.5% or more, and the effect of further pressing the pores at the 1 / 2 plate thickness position can be obtained. When the average reduction rate / pass within this temperature range is less than 3.5%, the rolling stress cannot be fully applied during rolling at a high temperature that is effective for pressing the pores, and pores are likely to remain at the end of rolling. This becomes the starting point of fracture, and it is difficult to reach the Charpy fracture transition temperature at the 1 / 2 plate thickness position: below -100°C. The average reduction rate / pass within this temperature range is preferably 4.0% or more, and more preferably 5.0% or more.

[0189] The upper limit of the average rolling reduction rate / pass in this temperature range is not particularly limited. From the viewpoint of manufacturing load, the average rolling reduction rate / pass in this temperature range is preferably 10% or less, and more preferably 8.0% or less.

[0190] [Rolling end temperature at 1 / 4 of plate thickness: Ar3 point or above] (optional condition)

[0191] In the hot rolling process, regarding the rolling end temperature at 1 / 4 of the plate thickness, when the rolling is ended at a temperature above the Ar3 point (°C) at the 1 / 4 position of the plate thickness, the effect of improving the brittle crack propagation stop characteristics can be more effectively obtained. During hot rolling, when the temperature at the 1 / 4 position of the plate thickness of the hot-rolled plate is lower than the Ar3 point (°C), processed ferrite is generated at the 1 / 4 position of the plate thickness, and the fraction of bainite that increases the X-ray intensity of the (110) plane is reduced, so the X-ray intensity ratio of the (110) plane at the 1 / 4 position of the plate thickness is reduced. As a result, excellent brittle crack propagation stop characteristics cannot be obtained. Furthermore, the lower the temperature, the greater the deformation resistance, so there is a problem of increasing the load on the hot rolling mill. It should be noted that the rolling end temperature is preferably above (Ar3 point + 20)°C.

[0192] The upper limit of the rolling end temperature is not particularly limited. From the viewpoint of rolling efficiency, the rolling end temperature is preferably (Ar3 point + 50)°C or lower, and more preferably (Ar3 point + 40)°C or lower.

[0193] <Cooling process>

[0194] Next, the hot rolled plate after hot rolling in the hot rolling process is cooled under the conditions that the cooling start temperature at the 1 / 2 thickness position is above the Ar3 point, the average cooling rate when the temperature at the 1 / 2 thickness position is in the temperature range of 700 to 500°C is above 2.0°C / s, and the cooling stop temperature at the 1 / 2 thickness position is below 500°C.

[0195] [Cooling start temperature: Ar3 point or above]

[0196] For the hot-rolled plate obtained through the above-mentioned hot rolling process, it is necessary to start cooling at a temperature at which the temperature at the 1 / 2 position of the plate thickness is above the Ar3 point (°C). When the cooling start temperature is lower than the Ar3 point (°C), the strength cannot be improved because a large amount of ferrite is generated in the steel. As a result, the X-ray intensity ratio of the (211) plane decreases, and excellent brittle crack propagation stopping characteristics cannot be obtained. Therefore, the cooling start temperature is set to be above the Ar3 point (°C). The cooling start temperature is preferably above (Ar3 point + 10)°C, and preferably below (Ar3 point + 40)°C.

[0197] [Average cooling rate in the temperature range of 700-500°C: 2.0°C / s or more]

[0198] When the average cooling rate is less than 2.0°C / s when the temperature at the half-thickness position is within the temperature range from 700°C to the cooling stop temperature (500°C or less), a large amount of ferrite is generated in the steel due to slow cooling, and the volume fraction of bainite cannot be increased. As a result, the X-ray intensity ratio of the (211) plane decreases, and excellent brittle crack propagation stop characteristics cannot be obtained. In addition, the strength decreases.

[0199] On the other hand, from the viewpoint of causing phase transformation of most of the austenite structure and obtaining an effect that greatly contributes to the characteristics of the steel sheet, the temperature range for measuring the average cooling rate is set to a temperature range of 700 to 500°C.

[0200] That is, in the present invention, the average cooling rate in the temperature range of 700 to 500°C at the half thickness position is set to 2.0°C / s or more. This can increase the fraction of bainite, improve strength, develop the texture of the (211) plane, and improve the brittle crack propagation arrest characteristics. The average cooling rate in this temperature range is preferably 3.0°C / s or more.

[0201] It should be noted that the upper limit of the average cooling rate is not particularly limited. From the viewpoint of avoiding an increase in cooling cost due to excessive rapid cooling, the average cooling rate is preferably 20° C. / s or less, and more preferably 10° C. / s or less.

[0202] The average cooling rate outside the temperature range of 700 to 500° C. does not have a significant effect on the formation of bainite and is therefore not particularly limited, but is preferably 0.5 to 0.1° C. / s from the viewpoint of production efficiency.

[0203] [Cooling stop temperature: 500°C or less]

[0204] The cooling process needs to be carried out until the temperature at the position of 1 / 2 of the plate thickness reaches 500°C or less. In other words, it needs to be carried out until the cooling stop temperature reaches a temperature below 500°C. When the cooling stop temperature is greater than 500°C, a large amount of ferrite is generated in the steel, so the area fraction of bainite cannot be increased. As a result, the X-ray intensity ratio of the (211) plane decreases, and excellent brittle crack propagation stop characteristics cannot be obtained. In addition, the strength is reduced. The cooling stop temperature is preferably below 450°C, and more preferably below 400°C. On the other hand, there is no restriction on the lower limit of the cooling stop temperature. When the cooling stop temperature is too low, the shape of the steel plate deteriorates. Therefore, the cooling stop temperature is preferably above 200°C, and more preferably above 300°C.

[0205] Example

[0206] Next, the present invention will be specifically described based on examples. It should be noted that the following examples are preferred examples of the present invention, and the present invention is not limited to these examples.

[0207] The composition of the test steel is shown in Table 1, and the manufacturing conditions are shown in Table 2. Molten steel (steel symbols: A to AG) of each component composition shown in Table 1 is melted in a converter and made into steel raw materials by continuous casting. Then, a heating process, a hot rolling process and a cooling process are carried out in sequence under the manufacturing conditions shown in Table 2 to manufacture high-strength ultra-thick steel plates (steel symbols: 1 to 42) with plate thicknesses shown in Table 3. It should be noted that the blank column in Table 1 indicates that the elements are not intentionally added, and includes not only the case where the elements are not contained (i.e., 0%), but also the case where the elements are inevitably contained.

[0208]

[0209]

[0210] The obtained high-strength ultra-thick steel plates were evaluated for (1) strength, (2) toughness, (3) texture, (4) steel structure, and (5) brittle crack propagation arrest characteristics by the methods described below.

[0211] (1) Strength

[0212] A JIS 14A test piece of φ14 was cut from the obtained high-strength ultra-thick steel plate at a position 1 / 2 of the plate thickness in such a way that the direction of the long axis of the test piece was perpendicular to the rolling direction, and a tensile test was performed in accordance with the provisions of JIS Z 2241 (2011) to measure the yield strength (YS) and tensile strength (TS).

[0213] Here, a yield strength of 390 MPa or more was evaluated as high strength, and a tensile strength of 570 MPa or more was evaluated as high strength.

[0214] (2) Toughness

[0215] The toughness was evaluated at the Charpy fracture transition temperature at the position of 1 / 2 of the plate thickness.

[0216] A JIS No. 4 impact test piece was cut from the 1 / 2 thickness position of the obtained high-strength ultra-thick steel plate in such a way that the direction of the long axis of the test piece was parallel to the rolling direction, and a Charpy impact test was performed in accordance with the provisions of JIS Z 2242 (2005) to obtain the Charpy fracture transition temperature (vTrs) in the range of -40°C to -160°C. It should be noted that three tests were performed for one test temperature, and the brittle fracture rate was calculated from the average value of the three tests.

[0217] Here, vTrs ≤ -100°C was evaluated as excellent low-temperature toughness.

[0218] (3) Texture

[0219] The texture was evaluated by measuring the X-ray intensity ratio of the (211) plane at a position of 1 / 2 of the plate thickness of the steel plate.

[0220] From the obtained high-strength ultra-thick steel plate, a plate-shaped sample having a plate thickness of 1 mm at a position 1 / 2 of the plate thickness, 22 mm in a direction parallel to the rolling direction, and 25 mm in a direction perpendicular to the rolling direction was cut, and the surface parallel to the surface of the sample was mechanically polished and electrolytically polished to prepare a test piece for X-ray diffraction. Using this test piece, an X-ray diffraction measurement was carried out using an X-ray diffraction device using a Mo ray source, and the X-ray intensity ratio of the (211) plane was obtained.

[0221] In addition, the X-ray intensity ratio of the (110) plane at a position of 1 / 4 of the plate thickness of the steel plate was measured.

[0222] From the obtained high-strength ultra-thick steel plate, a plate-shaped sample having a plate thickness of 1 mm at a position 1 / 4 of the plate thickness, 22 mm in a direction parallel to the rolling direction, and 25 mm in a direction perpendicular to the rolling direction was cut, and the surface parallel to the surface of the sample was mechanically polished and electrolytically polished to prepare a test piece for X-ray diffraction. Using this test piece, an X-ray diffraction measurement was carried out using an X-ray diffraction device using a Mo ray source, and the X-ray intensity ratio of the (110) plane was obtained.

[0223] (4) Steel structure

[0224] [Steel Structure]

[0225] The steel structure at the position of 1 / 2 of the plate thickness was measured as follows.

[0226] The sample is cut from the center of the width of the steel plate and at the 1 / 2 position of the plate thickness in such a way that the surface perpendicular to the rolling direction becomes the observation surface. The size of the sample is 20 mm in the direction of the plate thickness, 10 mm in the direction parallel to the rolling direction, and 1 mm in the direction perpendicular to the rolling direction. The surface of the sample perpendicular to the rolling direction is mirror-polished, and then an optical microscope photograph of the metal structure exposed by corrosion with nitric acid alcohol solution is taken. The shooting part is at the 1 / 2 position of the plate thickness, and the magnification is 200 times. Based on the obtained photos, the structure exposed in the form of white blocks is regarded as ferrite, and the remaining part is regarded as bainite. The area fraction is calculated by image analysis, thereby evaluating the area fraction of the bainite phase and the ferrite phase.

[0227] In addition, the steel structure at the position of 1 / 4 of the plate thickness was measured as follows.

[0228] The sample is cut from the center of the width of the steel plate and at 1 / 4 of the plate thickness in such a way that the surface perpendicular to the rolling direction becomes the observation surface. The size of the sample is 20 mm in the plate thickness direction, 10 mm in the direction parallel to the rolling direction, and 1 mm in the direction perpendicular to the rolling direction. The surface perpendicular to the rolling direction of the sample is mirror-polished, and then an optical microscope photograph of the metal structure exposed by corrosion with nitric acid alcohol solution is taken. The shooting part is at 1 / 4 of the plate thickness, and the magnification is 200 times. The area fraction of the bainite phase and the ferrite phase is evaluated by image analysis of the obtained photographs.

[0229] [Average grain size of bainite]

[0230] The average grain size of bainite grains at a position of 1 / 2 of the plate thickness is measured as follows.

[0231] The sample is cut from the center of the width of the steel plate and the 1 / 2 position of the plate thickness in such a way that the surface perpendicular to the rolling direction becomes the observation surface. The size of the sample is 20 mm in the plate thickness direction, 10 mm in the direction parallel to the rolling direction, and 1 mm in the direction perpendicular to the rolling direction. The surface perpendicular to the rolling direction of the sample is mirror-polished, and then EBSP analysis is performed on the 1 / 2 position of the plate thickness under the following conditions. From the obtained crystal orientation diagram, the equivalent circle diameter of the structure surrounded by the large-angle grain boundary with an orientation difference of more than 15° with the adjacent grains is obtained, and the average value of the equivalent circle diameter in the following analysis area is taken as the average effective crystal grain size.

[0232] (EBSP condition)

[0233] Accelerating voltage: 20KV, irradiation current: 50nA

[0234] Beam diameter: 50nm

[0235] Analysis area: 1mm×1mm area at the center of the plate thickness

[0236] Step size: 0.4μm

[0237] In addition, the average grain size of bainite grains at a position of 1 / 4 of the plate thickness was measured as follows.

[0238] The sample is cut from the center of the width of the steel plate and the 1 / 4 position of the plate thickness in such a way that the surface perpendicular to the rolling direction becomes the observation surface. The size of the sample is 20 mm in the plate thickness direction, 10 mm in the direction parallel to the rolling direction, and 1 mm in the direction perpendicular to the rolling direction. The surface perpendicular to the rolling direction of the sample is mirror-polished, and then EBSP analysis is performed on the 1 / 4 position of the plate thickness under the following conditions. From the obtained crystal orientation diagram, the equivalent circle diameter of the structure surrounded by large-angle grain boundaries with an orientation difference of more than 15° with adjacent grains is obtained, and the average value of the equivalent circle diameter in the following analysis area is taken as the average effective crystal grain size.

[0239] (EBSP condition)

[0240] Accelerating voltage: 20KV, irradiation current: 50nA

[0241] Beam diameter: 50nm

[0242] Analysis area: 1mm×1mm area at the center of the plate thickness

[0243] Step size: 0.4μm

[0244] [Equivalent circular diameter of the largest pore]

[0245] In the detection of defects inside the steel plate, ultrasonic flaw detection is mostly used because it can be inspected non-destructively. However, in this embodiment, in order to accurately confirm the state of the defective part, direct observation is performed to measure the number density of pores. First, at the 1 / 2 position of the plate thickness of the rolled material, 1 to 2 cross sections are cut from the observation sample parallel to the plate width direction, and mirror polishing is performed. Next, the prepared sample is observed using an optical microscope and photographed. The magnification is 400 times. The obtained photographs are subjected to image analysis to find the equivalent circular diameter of each existing pore, and the equivalent circular diameter of the largest pore is calculated.

[0246] (5) Brittle crack propagation arrest characteristics

[0247] The brittle crack propagation arrest characteristic was evaluated by determining the Kca value.

[0248] In order to evaluate the brittle crack propagation arrest characteristics, a temperature gradient standard ESSO test was performed to obtain the Kca value (Kca(-10℃) at -10℃ (N / mm 3 / 2 )).

[0249] Three test pieces were cut from each of the obtained high-strength and ultra-thick steel plates. The dimensions of the test piece were total thickness × L: 500 × W: 500 (mm). The Kca value was determined from the results of the three tests.

[0250] Here, the value of Kca (-10°C) is 8400 N / mm 3 / 2 The above test bodies were evaluated to be excellent in brittle crack propagation arrest characteristics.

[0251] Table 3 shows the test results.

[0252]

[0253] The results shown in Table 3 show the following. In the case of the examples of the present invention (manufacturing No. 1 to 17), the component composition and manufacturing conditions are within the scope of the present invention, and the texture at the 1 / 2 position of the plate thickness satisfies the X-ray intensity ratio of the (211) plane: 1.60 or more, and the steel structure at the above-mentioned 1 / 2 position of the plate thickness is also obtained. As a result, the yield strength at the 1 / 2 position of the plate thickness is 390 MPa or more, the Charpy fracture transformation temperature at the 1 / 2 position of the plate thickness is -100°C or less, and the Kca (-10°C) value is 8400 N / mm 3 / 2 The above characteristics.

[0254] On the other hand, in the case of comparative examples (manufacturing Nos. 18 to 42), one or more of the component compositions and manufacturing conditions were outside the scope of the present invention, so the texture and steel structure at the 1 / 2 thickness position could not be obtained, and the target properties at the 1 / 2 thickness position were not met.

Claims

1. A high-strength and extremely thick steel plate, It has a composition containing, in mass%, C: 0.040 to 0.150%, Si: 0.02 to 0.50%, Mn: 1.00 to 2.50%, P: 0.020% or less, S: 0.010% or less, Al: 0.010 to 0.100%, N: 0.0010 to 0.0100% and O: 0.0100% or less, and Ceq defined by formula (1) is 0.480 to 0.560%, and the balance is Fe and inevitable impurities, The texture has an X-ray intensity ratio of the (211) plane in the rolled surface at a position of 1 / 2 of the plate thickness of 1.60 or more, and having a steel structure at a position of 1 / 2 of the plate thickness as described below, wherein the steel structure at the position of 1 / 2 of the plate thickness is a mixed structure consisting of 80 to 100% of a bainite phase and 0 to 20% of a ferrite phase in terms of area fraction, the average grain size of bainite grains surrounded by grain boundaries with an orientation difference of 15° or more is 20 μm or less, and the equivalent circle diameter of the largest pore remaining at the position of 1 / 2 of the plate thickness is 200 μm or less, The thickness of the high-strength extra-thick steel plate is greater than 100 mm. The yield strength at the half thickness position is 390 MPa or more, the Charpy fracture transition temperature at the half thickness position is vTrs≤-100℃, and the Kca (-10℃) value is 8400N / mm 3 / 2 above, Ceq=C+Mn / 6+Cu / 15+Ni / 15+Cr / 5+Mo / 5+V / 5…(1) Here, C, Mn, Cu, Ni, Cr, Mo, and V in formula (1) represent the content (mass %) of each element, and the content of an element not contained is set to 0.

2. The high-strength extra-thick steel plate according to claim 1, wherein: In addition to the above-mentioned component composition, one or two selected from the following Group A and Group B are contained in terms of mass %, Group A: one or more selected from the group consisting of Ti: 0.030% or less, Nb: 0.050% or less, Cu: 2.00% or less, Ni: 2.50% or less, and Cr: 2.00% or less; Group B: one or more selected from the group consisting of Mo: 0.50% or less, V: 0.50% or less, W: 0.50% or less, Co: 0.50% or less, B: 0.0100% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, and REM: 0.0200% or less.

3. The high-strength ultra-thick steel plate according to claim 1 or 2, wherein: In the texture, the X-ray intensity ratio of the (110) plane in the rolled surface at a position of 1 / 4 of the plate thickness is 0.90 or more, The steel structure at the 1 / 4 thickness position is a mixed structure composed of 80 to 100% of a bainite phase and 0 to 20% of a ferrite phase in terms of area fraction, and the average grain size of bainite grains surrounded by grain boundaries with an orientation difference of 15° or more is 20 μm or less.

4. A method for producing a high-strength and ultra-thick steel plate, which is the method for producing a high-strength and ultra-thick steel plate according to any one of claims 1 to 3, wherein: The steel material having the above composition is heated to a heating temperature of 1000 to 1200° C. Next, hot rolling is carried out under the conditions that the rolling start temperature at the position of 1 / 2 thickness is (Ar3 point + 100) ° C or more, the cumulative reduction rate when the temperature at the position of 1 / 2 thickness is within the austenite recrystallization temperature range is 5.0% or more, the cumulative reduction rate when the temperature at the position of 1 / 2 thickness is within the austenite non-recrystallization temperature range is 50.0% or more, and the rolling end temperature at the position of 1 / 2 thickness is Ar3 point or more, and the thickness of the steel billet is 350 mm or more, and the reduction ratio representing the ratio of the thickness of the steel billet to the thickness of the final product is 3.25 or more and less than 4.

00. Next, cooling is carried out under the conditions that the cooling start temperature at the 1 / 2 thickness position is above the Ar3 point, the temperature at the 1 / 2 thickness position is in the temperature range of 700 to 500°C, the average cooling rate is above 2.0°C / s, and the cooling stop temperature at the 1 / 2 thickness position is below 500°C.

5. The method for producing a high-strength ultra-thick steel plate according to claim 4, wherein: The hot rolling is further performed under the conditions that the average reduction ratio / pass is 3.5% or more when the temperature at the half-thickness position is within the austenite recrystallization temperature range and the rolling end temperature at the quarter-thickness position is Ar3 point or more.

Citation Information

Patent Citations

  • Steel plate having excellent arrest property and its manufacturing method

    JP2002256375A

  • High-strength thick steel plate having excellent brittle crack propagation-stopping performance, and method for producing the same

    JP2008169467A

  • Steel having excellent brittle crack arrest property, and method of producing the same

    JP2011184754A

  • Method for manufacturing thick steel plate

    JP2012172258A

  • Production method for thick steel plate

    WO2011096456A1